Plan de factibilidad para la creación de una nueva línea de productos en la microempresa láctea Santa Ivonne de la parroquia Guaytacama. - Casa Sopalo, Fernanda Aracely (2020)
The present investigation determined the feasibility to create a new line of dairy products: pasteurized milk and yogurt with fruit in the microenterprise "SANTA IVONNE" of Guaytacama parish, in order to expand its different products made by milk, because the enterprise has the raw material. For the execution of this project, the analytical-synthetic method was used, which helped to explore grouped data of the dairy sector in which the market wanted to participate, through this methodology the productive potential could be demonstrated, considering two relevant indices for the Industry analysis: milk consumption rate per person annually (17.67% liters) yogurt (4.57% liters) and cheese (1.61% kilos), industry growth rate (3.4% annual). Consecutively, the demand for each of the products was identified. Then it is proceeded to determine the productive capacity of the microenterprise through unsatisfied demand indicating annual percentages that are intended to cover, also necessary requirements for the development of the new product line were detailed. Subsequently, the viability of the project was determined based on the aforementioned indices that encouraged the creation of the product, applying a financial evaluation with main indicators resulting in favorable figures for its viability and sustainability: VAN with a value of ($ 37,285, 96) and IRR with a percentage of (27%), an acceptable result to carry it out and thus strengthen at dairy production economy at Guaytacama parish.